2014
DOI: 10.1007/s11626-013-9730-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of static magnetic fields on canine and equine mesenchymal stem cells derived from adipose tissue

Abstract: The aim of this study was to evaluate the proliferation rate and morphological changes of adipose-derived mesenchymal stem cells of canine and equine origin (Eq- and CaAdMSC). Investigated cells were exposed to a static magnetic field (MF) with the intensity of 0.5 T. Proliferation activity of cells was determined with the Alamar Blue assay. Obtained results, normalized in respect to the control culture, showed that EqAdMSC exposed to MF maintained a high proliferation status, whereas proliferation activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…The exposure system used in this study was previously described by Marędziak et al [25]. A pair of permanent neodymium magnets with a known magnetic polarization vector was used to expose the cells to SMF.…”
Section: Static Magnetic Field Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The exposure system used in this study was previously described by Marędziak et al [25]. A pair of permanent neodymium magnets with a known magnetic polarization vector was used to expose the cells to SMF.…”
Section: Static Magnetic Field Exposurementioning
confidence: 99%
“…Thus, searching for factors able to enhance cell viability seems to be essential when application of MSCs in the field of regenerative medicine is considered. In our previous studies we have demonstrated that ASCs proliferation rate and their population doubling time (PDT) are distinctly increased when treated with a static magnetic field (SMF) [25]. It was previously shown that SMF might affect the behavior of cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…Subcutaneous adipose tissue was collected from the tail base area, according to standard surgical procedure, using local anesthesia induced by 2% lignocaine (Polfa S.A., Poland) [35]. The total amount of collected tissue samples was equal 3 grams.…”
Section: Isolation Of Adipose-derived Stromal Cells and Immunophenotymentioning
confidence: 99%
“…According to previous studies [35] the first 24 hr after isolation equine stem cells were maintained in Dulbecco's Modified Eagle's Medium (DMEM) with Nutrient F-12, whereas DMEM containing 4500 mg/L of glucose was applied for the secondary cell culture. The media were supplemented with 10% of fetal bovine serum (FBS), and 1% of antibiotic-antimycotic solution.…”
Section: Propagation Of Equine Adipose Derived Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…The interest in the variation biological effects of non-ionizing electromagnetic fields (EMFs) on the whole organism, as well as on cellular systems, has considerably increased in recent years in consideration of their probable health risk for humans (Pagliara et al, 2009). Several studies have shown that MF has an influence on a large variety of cellular functions; nevertheless the its exact mechanism(s) still is not clear (Marędziak et al, 2014). Few studies exist on the effects of static magnetic fields (SMFs) on living cells and tissues, compared with low-frequency magnetic fields.…”
Section: Introductionmentioning
confidence: 99%